Cholinergic enhancement of functional networks in older adults with mild cognitive impairment. Issue 6 (17th June 2013) - Pa, Judy; Berry, Anne S.; Compagnone, Mariana; Boccanfuso, Jacqueline; Greenhouse, Ian; Rubens, Michael T.; Johnson, Julene K.; Gazzaley, Adam
<x xml:space="preserve">Abstract</x> Objective The importance of the cholinergic system for cognitive function has been well documented in animal and human studies. The objective of this study was to elucidate the cognitive and functional connectivity changes associated with enhanced acetylcholine levels. We hypothesized that older adults with mild memory deficits would show behavioral and functional network enhancements with an acetylcholinesterase inhibitor treatment (donepezil) when compared to a placebo control group. Methods We conducted a 3‐month, double‐blind, placebo‐controlled study on the effects of donepezil in 27 older adults with mild memory deficits. Participants completed a delayed recognition memory task. Functional magnetic resonance imaging (fMRI) scans were collected at baseline prior to treatment and at 3‐month follow‐up while subjects were on a 10mg daily dose of donepezil or placebo. Results Donepezil treatment significantly enhanced the response time for face and scene memory probes when compared to the placebo group. A group‐by‐visit interaction was identified for the functional network connectivity of the left fusiform face area (FFA) with the hippocampus and inferior frontal junction, such that the treatment group showed increased connectivity over time when compared to the placebo group. Additionally, the enhanced functional network connectivity of the FFA and hippocampus significantly predicted memory response time at 3‐month follow‐up in the treatment group. Interpretation These findings suggest that increased cholinergic transmission improves goal‐directed neural processing and cognitive ability and may serve to facilitate communication across functionally‐connected attention and memory networks. Longitudinal fMRI is a useful method for elucidating the neural changes associated with pharmacological modulation and is a potential tool for monitoring intervention efficacy in clinical trials. ANN NEUROL 2013;73:762–773